Pengaruh Model Pembelajaran Savi Berbantuan Cafas terhadap Pemahaman Konsep Siswa - Eriawan, Dendy; Lisa Virdinarti Putra (JANACITTA, 2025)
Abstract Students' ability to understand concepts so they can apply their knowledge and understanding of mathematics. The aim of this research is to determine the effect of the SAVI (somatic, auditory, visual and intellectual) learning model assisted by Canva on students' conceptual understanding. The subjects of this research were 28 students in class II A and 28 students in class II B at SDN Bandungan 01. The type of data collected in this research is quantitative and experimental methods. Data collection techniques in this research are Test (Pre Test and Post Test) and Non Test (Observation, Questionnaire and Documentation). The data analysis techniques in this research are normality test, homogeneity test, hypothesis test in the form of independent sample t-test and simple linear regression test. The results of the research show that: (1) There are differences in students' understanding of concepts using the SAVI learning model assisted by Canva media. This is proven by the results of the Independent Sample T-Test with a significance level of less than 0.05, namely 0.000 < 0.05. So it can be concluded that there is a significant difference between the experimental class and control class learning groups, where the average value for the experimental class is 91.11 greater than the control class average of 82.75. (2) There is an influence of using the SAVI learning model assisted by Canva media on students' understanding of concepts. This is proven by the results of the Simple Linear Regression Test with a significance value of less than 0.05, namely 0.008 < 0.05. The conclusion of this research is that the SAVI (somatic, auditory, visual and intellectual) learning model assisted by Canva media is effective in influencing students' concept understanding abilities. Abstrak Kemampuan siswa untuk memahami konsep sehingga mereka dapat menerapkan pengetahuan dan pemahaman mereka tentang matematika. Tujuan penelitian ini adalah untuk mengetahui pengaruh model pembelajaran SAVI (Somatik, Auditory, Visual, Intelektual) berbantuan Cafas terhadap pemahaman konsep siswa. Populasi dalam penelitian ini yaitu siswa SD N Bandungan 01. Sampel penelitian ini adalah 28 siswa kelas II A dan 28 siswa II B SDN Bandungan 01. Jenis data yang dikumpulkan dalam penelitian ini adalah kuantitatif, dan metode eksperimen. Teknik pengumpulan data dalam penelitian ini adalah Tes (Pre Test dan Post Test) dan Non Test (Observasi, Angket, dan Dokumentasi). Teknik analisis data pada penelitian ini adalah uji normalitas, uji homogenitas, uji hipotesis yang berupa uji independent sample t-test dan uji regresi linier sederhana. Hasil penelitian menunjukkan bahwa: (1) Terdapat perbedaan pemahaman konsep siswa siswa dengan penggunaan model pembelajaran SAVI berbantuan media Canva. Perihal ini dibuktikan dengan hasil Uji Independent Sample T-Test dengan taraf nilai signifikansi kurang dari 0,05 yaitu 0,000 < 0,05. Sehingga dapat disimpulkan terdapat perbedaan yang signifikan antara kelompok belajar kelas eksperimen dan kelas kontrol, yang dimana nilai rataan untuk kelas eksperimen 91,11 lebih besar daripada rataan kelas kelas kontrol 82,75. (2) Terdapat pengaruh penggunaan model pembelajaran SAVI berbantuan media Cafas terhadap pemahaman konsep siswa. Perihal ini dibuktikan dengan hasil Uji Regresi Linier Sederhana dengan nilai signifikansi kurang dari 0,05 yaitu 0,008 < 0,05. Simpulan dari penelitian ini adalah terdapat pengaruh model pembelajaran SAVI (Somatik, Auditory, Visual, Intelektual) berbantuan media Cafas terhadap kemampuan pemahaman konsep siswa.